2014
DOI: 10.1021/ja507665a
|View full text |Cite|
|
Sign up to set email alerts
|

Bifunctional Porphyrin Catalysts for the Synthesis of Cyclic Carbonates from Epoxides and CO2: Structural Optimization and Mechanistic Study

Abstract: We prepared bifunctional Mg(II) porphyrin catalysts 1 for the solvent-free synthesis of cyclic carbonates from epoxides and CO2. The activities of 1d, 1h, and 1i, which have Br(-), Cl(-), and I(-) counteranions, respectively, increased in the order 1i < 1h < 1d. Catalysts 1d and 1j-m, which bear four tetraalkylammonium bromide groups with different alkyl chain lengths, showed comparable but slightly different activities. Based on the excellent catalyst 1d, we synthesized Mg(II) porphyrin 1o with eight tetraalk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
263
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 423 publications
(277 citation statements)
references
References 105 publications
14
263
0
Order By: Relevance
“…The same issue was addressed by Ema and co-workers, 51 Alternative strategies to prepare diastereo-pure COCs have also been reported, including the Pd(II) catalyzed coupling of CO with diols, as described by Dibenedetto and co-workers. 60 Although modest success was observed in terms of substrate scope and yields, this oxidative carbonylation of 1,2-and 1,3-diols catalyzed by palladium iodide in conjunction with KI gave access to diastereo-pure COCs starting from diastereoisomeric mixtures of the substrates (Scheme 12; T = 100 ºC, DMA, PdI 2 = KI = 10 mol%, p(CO 2 ) = 2.0 MPa of a 1:4 CO-air mixture).…”
Section: Methodsmentioning
confidence: 82%
See 1 more Smart Citation
“…The same issue was addressed by Ema and co-workers, 51 Alternative strategies to prepare diastereo-pure COCs have also been reported, including the Pd(II) catalyzed coupling of CO with diols, as described by Dibenedetto and co-workers. 60 Although modest success was observed in terms of substrate scope and yields, this oxidative carbonylation of 1,2-and 1,3-diols catalyzed by palladium iodide in conjunction with KI gave access to diastereo-pure COCs starting from diastereoisomeric mixtures of the substrates (Scheme 12; T = 100 ºC, DMA, PdI 2 = KI = 10 mol%, p(CO 2 ) = 2.0 MPa of a 1:4 CO-air mixture).…”
Section: Methodsmentioning
confidence: 82%
“…To further enhance the catalytic activity of these bifunctional Mg(II) porphyrin systems, a Mg(II) porphyrin complex ligated to eight tetraalkylammonium bromide groups (i.e., a 1:8 LA/co-cat site ratio) was prepared. 51 Consequently, owing to the increased number of anionic nucleophilic centers tightly coordinated to the cationic catalyst molecule, higher TON were achieved after t = 24 h (TON = 138000) and an increased initial TOF of 19000 h -1 (conditions: cat = 0.0005 mol%, p(CO 2 ) = 1.7 MPa, T = 120 ºC). For these bifunctional Mg(porphyrin) based catalysts, the authors suggested a cooperative effect of embedding the nucleophilic moiety (Br) and the Lewis acidic metal center in a tight coordination sphere, leading to a simultaneous epoxide activation/nucleophile attack.…”
Section: Development Of Improved Reactivity In Coc Synthesismentioning
confidence: 99%
“…However, when further raising the CO2 pressure up to 6.0-7.0 MPa, an obvious negative influence appeared (entries 9, 10), which could be explained that the dissolved adjacent supercritical CO2 molecules act as a diluent, and the dilution of the epoxide and catalysts likely contributed to the drop in reaction rate and gave a negative impact. 30 The positive impact should be more significant at low CO2 pressure while the negative impact at high pressure. Under the conditions used, a low CO2 pressure of 1.0 MPa is sufficient for the synthesis of PC.…”
Section: (C) Effects Of Reaction Parametersmentioning
confidence: 99%
“…[1] While several approaches exist to activate and reduce this inert molecule by hydrides, [2] to incorporate it into carbamides, [3] to polymerize it with epoxides to polycarbonates [4] or to form cyclic carbonates [5] with it, reduction and/or disproportionation of CO 2 to form carbon monoxide, oxide, carbonate, or oxalate appears equally attractive. In this case, the metal complexes provide the electronic platform for reduction and transformation of CO 2 in the absence of additional electron providing substrates.…”
Section: Introductionmentioning
confidence: 99%